Teknologi Digital Sarana Menanamkan Nilai-Nilai Pancasila - Bambang Mudjiyanto; Amri Dunan (PRoMEDIA, 2021)
AbstractInstilling the values of Pancasila ideology in the digital era through the internet is very much needed. Through the right formulas and methods, all Indonesian people, including the millennial generation, are able to understand and implement the values of Pancasila in the life of society, nation and state. In its implementation, it requires superior programs in the structural aspects of education, and exemplary. It takes a creative way, especially one that is closer to the younger generation by using technology, science, social media, and creative approaches. Pancasila as an ideology can be articulated with various forms of real life. As an open ideology, Pancasila cannot be separated from the influence of values that develop in society today. The precepts of divinity are the spirit of nationality, while the precepts of humanity are national character and the precepts of unity are national bonds. As for the fourth precept regarding democracy as a medium or instrument of Indonesian nationality, the fifth precept of social justice is the goal of Indonesian nationality. The Indonesian people must be strong in maintaining the Pancasila ideology so that it is not eroded or lost by the times.Keywords: Digital Technology, Pancasila ValuesAbstraksiPenanaman nilai-nilai ideologi Pancasila pada era digital melalui media internet sangat dibutuhkan. Melalui formula dan metode yang tepat maka seluruh masyarakat Indonesia termasuk generasi milenial, mampu memahami dan mengimplementasikan nilai-nilai Pancasila dalam kehidupan bermasyarakat, berbangsa dan bernegara. Dalam pelaksanaannya memerlukan program-program unggulan pada aspek struktural pendidikan, dan keteladanan. Butuh cara kreatif, khususnya yang mendekatkan ke generasi muda dengan pendekatan teknologi, ilmu pengetahuan, media sosial, dan kreatif. Pancasila sebagai ideologi dapat diartikulasikan dengan berbagai bentuk kehidupan nyata. Sebagai ideologi terbuka, Pancasila tidak bisa lepas dari pengaruh nilainilai yang berkembang di masyarakat pada zaman kekinian. Pada sila Ketuhanan merupakan roh kebangsaan, sedangkan sila kemanusiaan adalah watak kebangsaan serta sila persatuan merupakan ikatan kebangsaan. Adapun sila keempat mengenai demokrasi merupakan media atau alat kebangsaan Indonesia, berikutnya sila kelima keadilan sosial merupakan tujuan dari kebangsaan Indonesia. Masyarakat Indonesia harus kukuh dalam menjaga ideologi Pancasila agar tidak tergerus atau hilang oleh zaman.Kata Kunci: Teknologi Digital, Nilai-nilai Pancasila